1977
DOI: 10.1007/bf01565928
|View full text |Cite
|
Sign up to set email alerts
|

Arterial epigastricocavernous anastomosis for the treatment of sexual impotence

Abstract: Previous histologic and phalloarteriographic studies that we have performed suggest that stenoses and occlusions of the arteries supplying the penis play a very important role in the etiology of sexual impotence in many patients. This report describes the results of direct arterial anastomosis to the cavernous bodies of the penis, using the inferior epigastric artery and microsurgical technique, in 21 impotent males ranging in age from 40 to 63 years. The objective of the operation was to increase basal penile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
6

Year Published

1983
1983
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(42 citation statements)
references
References 0 publications
1
35
0
6
Order By: Relevance
“…[1] on successful penile revascularization in 1974, more than 15 different operative techniques have been developed with extremely varying success rates [1][2][3].In a previous study,we reported our surgical results using the modified Furlow-Fisher technique in 25 patients with 4-year follow-up. In that study, which was the first report on this issue, the importance of CC-EMG findings in the preoperative evaluation was discussed and the IIEF score was used for the postoperative evaluation of the patients who had undergone revascularization surgery [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] on successful penile revascularization in 1974, more than 15 different operative techniques have been developed with extremely varying success rates [1][2][3].In a previous study,we reported our surgical results using the modified Furlow-Fisher technique in 25 patients with 4-year follow-up. In that study, which was the first report on this issue, the importance of CC-EMG findings in the preoperative evaluation was discussed and the IIEF score was used for the postoperative evaluation of the patients who had undergone revascularization surgery [15].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first report of Michal et al . [1] on successful penile revascularization in 1974, more than 15 different operative techniques have been developed, with extremely varying success rates [2][3][4]. Deep dorsal vein arterializations have been described by Virag et al .…”
Section: Introductionmentioning
confidence: 99%
“…Newman, Northup and Devlin reported a maintenance rate of 12 ml min À1 and an induction rate of 20-50 ml min À1 . 45 Michel et al 49 revealed a maintenance rate of 50-70 % and an induction rate of 45-170 ml min…”
mentioning
confidence: 97%
“…This procedure also proved to be unphysiological and, at best, leads to incurable priapism. Michal et al [18] modified their approach by performing anastomosis between the inferior epigastric artery and one of the dorsal arteries ( fig. 20).…”
Section: Survey Of the Different Surgical Concepts For The Treatment mentioning
confidence: 99%